Five Supplements and Multiple Psychotic Symptoms: A Case Report - Wong, Michelle K. (Prim Care Companion CNS Disord, 2016)
Dietary supplements, including vitamins, minerals, herbs, amino acids, and enzymes, have become increasingly more common and are used by approximately half of the US population. About three-fourths of supplements are obtained with no prescription from a physician, which raises medical concerns regarding safety as these products do not require US Food and Drug Administration approval. Common reasons for taking dietary supplements include improved mood, improved mental function, depression relief, anxiety reduction, and treatment of simple and migraine headaches. The use of herbs for medicinal purposes has a long-standing history among many cultures. We present the case of a 43-year-old man, who was taking dietary supplements, with a 6-month history of psychotic symptoms that increasingly caused impairment in functioning and eventually led to involuntary hospitalization. The published data with regard to supplements causing psychosis, herb-to-herb interaction, and reliability of herbal supplement manufacturers are discussed.